PENGARUH PENYULUHAN PERPAJAKAN, PELAYANAN FISKUS, DAN PERSEPSI WAJIB PAJAK ORANG PRIBADI ATAS PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI KPP PRATAMA JAKARTA KEMBANGAN - Muti’ab, Muti’ab (Teropong : Jurnal Manajemen dan Bisnis, 2020)
Purpose of this study was to analyze the effect of the tax extension, the service tax authorities, and the perception ofindividual taxpayers on tax audits and individual tax compliance. The population of this research is personal tax payers who registered at KPP Pratama Jakarta Kembangan. Sampling Method which used is Non Probability Sampling. Number of samples mentioned as many as 30 persons. Primary data collections method which used on this research is questionnaire survey method by using questionary papers. Data analysis method which used on this research is multiple linear regression analysis. The analysis showed that tax counceling, tax services. perception ofpersonal tax payer about tax audit give a great effect on obedience ofpersonal tax payer. Keywords: tax counceling, tax services, perception of personal tax payer about tax audit, obedience of personal tax payer